Rates of adverse events in patients with Ulcerative Colitis undergoing colectomy during treatment with Tofacitinib vs Biologics: A multicenter observational study - Dragoni, Gabriele (2024)
INTRODUCTION: Patients with ulcerative colitis (UC) receiving immunosuppressive drugs are at substantial risk of colectomy. We aimed to assess the risk of postoperative complications of tofacitinib exposure before colectomy in comparison with biologics. METHODS: A multicenter, retrospective, observational study was conducted in patients with UC who underwent total colectomy for medically refractory disease, exposed to tofacitinib or a biologic before surgery. Primary outcome was the occurrence of any complication within 30 (early) and 90 (late) days after surgery. Secondary outcomes were the occurrence of infections, sepsis, surgical site complications, venous thromboembolic events (VTE), hospital readmissions, and redo surgery within the same timepoints. RESULTS: Three hundred one patients (64 tofacitinib, 162 anti-tumor necrosis factor-alpha agents, 54 vedolizumab, and 21 ustekinumab) were included. No significant differences were reported in any outcome, except for a higher rate of early VTE with anti-tumor necrosis factor-alpha agents (P = 0.047) and of late VTE with vedolizumab (P = 0.03). In the multivariate analysis, drug class was not associated with a higher risk of any early and late complications. Urgent colectomy increased the risk of any early (odds ratio [OR] 1.92, 95% confidence interval [CI] 1.06-3.48) complications, early hospital readmission (OR 4.79, 95% CI 1.12-20.58), and early redo surgery (OR 7.49, 95% CI 1.17-47.85). A high steroid dose increased the risk of any early complications (OR 1.96, 95% CI 1.08-3.57), early surgical site complications (OR 2.03, 95% CI 1.01-4.09), and early redo surgery (OR 7.52, 95% CI 1.42-39.82). Laparoscopic surgery decreased the risk of any early complications (OR 0.54, 95% CI 0.29-1.00), early infections (OR 0.39, 95% CI 0.18-0.85), and late hospital readmissions (OR 0.34, 95% CI 0.12-1.00). DISCUSSION: Preoperative tofacitinib treatment demonstrated a postoperative safety profile comparable with biologics in patients with UC undergoing colectomy.